Aktivitas Antagonisme Cendawan Endofit terhadap Cendawan Penyebab Bintik Mata Cokelat Daun Kopi: Antagonism Activity of Endophytic Fungi Against Pathogenic Fungus That Cause Coffee Brown Eye Spot - Asparita, Yulia Dwi; Aini, Luqman Qurata; Suharjono (Jurnal Fitopatologi Indonesia, 2025)
Antagonism Activity of Endophytic Fungi Against Pathogenic Fungus That Cause Coffee Brown Eye Spot Coffee is a high economic value commodity and is a source of foreign exchange for Indonesia. Coffee productivity and quality have decreased due to brown eye spot disease caused by fungi infection. One alternative method to overcome the growth of pathogenic fungi is to use endophytic fungi as an antagonistic biological agent. This study aims to identify the fungi causing coffee plant brown eye spot disease and its antagonistic endophytic fungi, and to evaluate the mechanisms and potential of antagonism. Pathogenic fungi were isolated from coffee leaves showing symptom of brown eye spot disease. Endophytic fungi were isolated from healthy leaves obtained from the Taji Village Coffee Plantation, Jabung District, Malang Regency. Each fungus was cultured and then purified using the monospore method. Pathogenic fungi isolates were selected based on the pathogenicity test. Endophytic fungi isolates were tested for their antagonistic properties against selected brown eye spot pathogenic fungi isolates and the endophytic fungus that had the highest potential to inhibit growth of the pathogenic fungi were identified based on 18S rDNA sequence similarity. The identification results show that the pathogenic fungus has 100% sequence similarity with Mycosphaerella coffeicola-PF2 while the antagonistic endophytic fungus has 99.94% similarity with Colletotrichum sp.-EF1. The endophytic fungi Colletotrichum sp. inhibits the growth of M. coffeicola by competition and mycoparasite mechanisms. The endophytic fungi Colletotrichum sp. can be developed as a biopesticide agent to control M. coffeicola which causes brown eyespot disease on coffee plant leaves.